Psychometric properties in instruments evaluation of reliability and validity - Souza, Ana Cláudia de; Alexandre, Neusa Maria Costa; Guirardello, Edinêis de Brito (Epidemiologia e serviços de saúde, 2017)
Measurement instruments play an important role in research, clinical practice and health assessment. Studies on the quality of these instruments provide evidence of how the measurement properties were assessed, helping the researcher choose the best tool to use. Reliability and validity are considered the main measurement properties of such instruments. Reliability is the ability to reproduce a result consistently in time and space. Validity refers to the property of an instrument to measure exactly what it proposes. In this article, the main criteria and statistical tests used in the assessment of reliability (stability, internal consistency and equivalence) and validity (content, criterion and construct) of instruments are presented, discussed and exemplified. The assessment of instruments measurement properties is useful to subsidize the selection of valid and reliable tools, in order to ensure the quality of the results of studies.